Effect of bacterial xylanase on the automated production of barley flour-enriched sandwich bread - Chambi-Rodriguez, Alex Danny; Coila-Tiña, Lizeth Vanessa; Sandoval-Sandoval, Palmira; Torres-Jiménez, Ana Mónica (Agronomía colombiana, 2024)
The aim of this research was to determine the effect of bacterial xylanase on the automated baking of barley flour-enriched sandwich bread. For this purpose, xylanase (0.02% to 0.04%) was added to the basic formulation of sandwich bread enriched with 10% whole barley flour. The resulting bread slices were subjected to image analysis to determine colorimetric properties, cell count, and sensory evaluation using a 9-point hedonic scale. A 0.03% xylanase addition produced a higher number of cells compared to other treatments. Regarding the colorimetric properties, no significant differences were observed, and the bread with 0.03% xylanase addition received the highest preference score in the sensory evaluation. In conclusion, bacterial xylanase has positive effects on bread, improving its overall quality. El objetivo del presente estudio fue determinar el efecto de la xilanasa bacteriana en el horneado automatizado de pan tipo molde enriquecido con harina de cebada. Para tal efecto se realizaron adiciones de xilanasa (0,02 al 0,04%) a la formulación básica de un pan de molde enriquecida con 10% de harina de cebada integral. A los panes obtenidos se les realizaron análisis de imágenes para determinar las propiedades cromáticas y el número de células, y se evaluó sensorialmente cada muestra en una escala hedónica de 9 puntos. El 0,03% de adición de xilanasa presentó mayor número de células en contraste con los demás tratamientos; respecto a las propiedades cromáticas, no hubo diferencias significativas y finalmente el pan con adición de 0,03% de xilanasa presentó la mayor preferencia en la evaluación sensorial. En conclusión, la xilanasa bacteriana genera efectos positivos en el pan, mejorando su calidad.